Teachers’ Work Practices in Kazakhstan: Some Comparative Insights from TIMSS 2011 to Guide Curriculum Implementation (Journal of Educational Sciences, 2018)
This paper2 looks at the different norms of practice between mathematics teachers in two countries, Kazakhstan and England. These differences pose challenges and opportunities for the implementationof a new secondary curriculum in Kazakhstan; a curriculum that has been shaped by and is grounded in prevailing practice in English educational system. The paper draws on survey data from the 2011 TIMSSexercise and relates it to our observations of classrooms in Kazakhstan over the last 5 years. The analysis draws on various cross-national studies of teachers’ work and studies of subject departments. Thepaper concludes with a discussion of the implications for successful curricula change and how it can be supported by an understanding of prevailing norms of practice. The paper also illustrates the continuedvalue of cross-national comparison of educational practices especially for relatively new nations. It questions the popular notion that global waves of policy solutions have washed, unimpeded and unchanged,across national borders.Key words: Comparative studies, teacher education, teaching practices, TIMSS.